GROWTH AND SURVIVAL RATE OF GIANT PRAWNS (Macrobrachium rosenbergii De Man) ON DIFFERENT STOCKING DENSITY - Novri Iswandi; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted for 30 days from september to october 2014 which was held at the Great Hall of Freshwater Aquaculture Sukabumi, West Java Province. The aim of this research was to determine the different stocking densities for growth and survival rate of Giant prawns (Macrobrachium rosenbergii De Man). The method used is the experimental method with completely randomized design (CRD) of the factor with 3 levels of treatment. The treatment were applied, namely P1 of 40 tail/m2, P2 of 60 tail/m2, P3 of 80 tail/m2.The best results showed that stocking density of40 tail/m2. Total absolute body weight, absolute body length, daily growth rate and survival rate was 5,5 grams, 2,65 cm, 2,25 %/day and 92,5 % respectively.Water quality parameters were recorded namely temperature is 24-26º C, pH 6-7,5 and dissolved oxygen (DO) from 4,3 to 4,8 ppm / l . Keywords: Giant prawns, stocking density, tokolan, growth